An Assessment of Preoperative and Postoperative Nutritional Status in Children with Cleft Lip and Palate - Khaleghnejad Tabari, Ahmad; Hatefi, Sayeh; Mohajerzadeh, Leili; Hassas-Yeganeh, Shaghayegh (Iranian Journal of Pediatric Surgery, 2015)
Background: Children with cleft lip and palate generally suffer from inappropriate and inadequate feeding, resulting in insufficient weight gain leading to malnutrition and poor growth. We aimed to evaluate the nutritional and growth status of cleft lip and palate children before and after reconstructive cleft lip and palate surgery. Methods: All cleft lip and palate children aging from birth up to 36 months who were admitted to a referral Children's Hospital were investigated by a nutritionist. Data were collected using a questionnaire. About 5-6 months after surgery, data regarding their height, weight, feeding status and feeding difficulties were collected by telephone. Statistical analysis was performed using SPSS 18 software. For qualitative variables we used frequency and percentage and for quantitative variables we measured mean and standard deviation. We used Paired Sample T-test for comparing weight differences before and after surgery. Results: In this study, formula was the most common type of feeding before and after surgery. Nasal regurgitation and insufficient sucking was the most common complaint of mother's before surgery, and also nasal regurgitation was reported as the most common difficulty after surgery, probably due to the need for reoperation. Bottle feeding was the most common method of feeding before and after surgery. After surgery only one mother claimed that her child spent more than 30 minutes for feeding. Weight for age of 18 children before surgery was lower than 5th percentile while after surgery this was reduced to 13 children. Also, there were significant differences between mean age before and after surgery which could implicate increase of weight after surgery. Conclusions: Our study demonstrates the results of surgical repair of cleft lip and palate on nutritional status in children.